2012
DOI: 10.1002/piq.20140
|View full text |Cite
|
Sign up to set email alerts
|

Examining big brother's purpose for using electronic performance monitoring

Abstract: We examined whether the reason offered for electronic performance monitoring (EPM) influenced participants' performance, stress, motivation, and satisfaction. Participants performed a data‐entry task in one of five experimental conditions. In one condition, participants were not electronically monitored. In the remaining conditions, participants were electronically monitored but the explanation varied. One group was told that they would be electronically monitored but were given no explanation. Another group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Over the past two decades, scholars have increasingly moved away from examining EPM dichotomously (present or absent) toward more precise exploration of the effects of EPM characteristics, such as the purpose (e.g., Bartels & Nordstrom, 2012; Holman, Chissick, & Totterdell, 2002), timing (e.g., Alder, 2007; Watson et al, 2013), target (e.g., Ambrose & Alder, 2000), intensity (e.g., Alge, Ballinger, & Green, 2004; Laird et al, 2018), scope (e.g., Moorman & Wells, 2003), control (e.g., McNall & Stanton, 2011), feedback delivery (e.g., Holman et al, 2002; Moorman & Wells, 2003), transparency (e.g., Lowry, Posey, Bennett, & Roberts, 2015; McNall & Roch, 2009), and clarity (e.g., Holman et al, 2002). Results from EPM research conducted over the past 20 years suggest that to understand the effects of a particular use of EPM, one must examine the psychological characteristics of that use.…”
Section: Conceptualizing Epmmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past two decades, scholars have increasingly moved away from examining EPM dichotomously (present or absent) toward more precise exploration of the effects of EPM characteristics, such as the purpose (e.g., Bartels & Nordstrom, 2012; Holman, Chissick, & Totterdell, 2002), timing (e.g., Alder, 2007; Watson et al, 2013), target (e.g., Ambrose & Alder, 2000), intensity (e.g., Alge, Ballinger, & Green, 2004; Laird et al, 2018), scope (e.g., Moorman & Wells, 2003), control (e.g., McNall & Stanton, 2011), feedback delivery (e.g., Holman et al, 2002; Moorman & Wells, 2003), transparency (e.g., Lowry, Posey, Bennett, & Roberts, 2015; McNall & Roch, 2009), and clarity (e.g., Holman et al, 2002). Results from EPM research conducted over the past 20 years suggest that to understand the effects of a particular use of EPM, one must examine the psychological characteristics of that use.…”
Section: Conceptualizing Epmmentioning
confidence: 99%
“…Research has demonstrated that purpose, and individual perceptions about purpose, influences reactions to EPM (McNall & Stanton, 2011; Wells et al, 2007). Researchers have examined EPM systems with a variety of purposes, including performance appraisals (e.g., Fenner, Lerch, & Kulik, 1993), punishment (e.g., Bartels & Nordstrom, 2012; McNall & Stanton, 2011), training (e.g., Thompson, Sebastianelli, & Murray, 2009), development (e.g., McNall & Roch, 2009; Wells et al, 2007), location tracking (e.g., Shirish, Chandra, & Srivastava, 2017), administration (e.g., Karim, 2015), sustainability (e.g., Bolderdijk, Steg, & Postmes, 2013), safety (e.g., Heflin, 2012), and EPM used for no clear purpose at all (e.g., McNall & Roch, 2007). Our typology organizes these purposes into four categories, described next: (a) performance appraisal, loss prevention, and profit ( performance ); (b) development, growth, and training ( development ); (c) administrative and safety ( admin and safety ); and (d) surveillance and authoritarian control ( surveillance ).…”
Section: Purposementioning
confidence: 99%
See 3 more Smart Citations